Personal values, wishes, and goals of patients with advanced lung cancer: a qualitative study - König, Mara; Siegle, Anja; Unsöld, Laura; Ludwig, Jan Ole; Deis, Nicole; Thomas, Michael; Poß-Doering, Regina; Villalobos Bollen, Matthias Americo (European journal of cancer care, 2024)
Objective. Oncology and palliative care guidelines for patients with incurable cancer recommend supporting patients at the end of life (EOL) by considering their personal values, wishes, and goals to facilitate decision making in advance care planning and patient-centered care. It is unclear, though, how to successfully address and integrate personal values in clinical practice. The aim of this study was to explore values, wishes, and goals from the perspective of patients with advanced lung cancer. Methods. Semistructured interviews were conducted with patients with advanced lung cancer and transcribed verbatim. The data were analysed using a structured content analysis. After identification of main categories, values were identified using Schwartz’s Theory of Basic Human Values as a theoretical framework. Results. Identified main categories were “the individual in medical care,” “living now,” and “coming to terms.” Values in the dimensions “conservation” and “openness to change” were described concerning patient-physician interaction, therapy goals, preparedness for EOL, and life goals. “Self-transcendence” values mainly related to caring for the burden on relatives. In general, patients showed reluctance in expressing information about personal values when communicating with physicians. Conclusion. Patients with advanced lung cancer engage in various ways to determine how they want and can influence their life and medical care. Different values and the associated wishes and goals play a crucial role in this context and should be taken into account by healthcare providers. The reluctance to express personal information in medical encounters underscores the need for a proactive attitude in physicians and improved interprofessional collaboration. The study was registered in the German register for clinical trials (DRKS00026993).
Online veröffentlicht: 9. August 2024
Gesehen am 11.02.2025